Changes in microbial and physicochemical properties during free-cell and encapsulated probiotic fermentation of red dragon fruit juice - Ong, Yien Yien (2014)
Red dragon fruit or red pitaya (Hylocereus polyrhizus) has gained its popularity in recent years because of its unique appearance and high nutrient contents (fiber, oligosaccharides, proline, potassium, sodium, and betacyanin). Most of the time, the fruit is consumed freshly but the shelf-life of the fruit is short (5 to 7 days at room temperature). A solution is proposed in this research to extend the shelf-life of the fruit by developing a probiotic beverage from red dragon fruit juice through fermentation. The development of probiotic beverage involves the selection of probiotic strains, the study of fermentation parameters and the improvement of the viability of the probiotic in fermented red dragon fruit juice. The selection of probiotic begins with the isolation and identification of lactic acid bacteria (LAB) from red dragon fruit as probiotics are mostly LAB. Bacteria were isolated on MRS agar and the species of the isolates was identified using biochemical tests, polymerase chain reaction (PCR), randomly amplified polymorphic DNA (RAPD) PCR, 16S rDNA sequencing, and restriction fragment length polymorphism (RFLP). Two species namely Enterococcus casseliflavus and Enterococcus gallinarum were isolated from red dragon fruit. Although the isolated LAB were found to be nonprobiotic strains, the suitability of red dragon fruit juice as medium for probiotic fermentation should not be disregarded. Hence, Lactobacillus casei was used as probiotic inoculums for the development of a non-dairy based probiotic beverage using red dragon fruit juice as fermentation medium. Several parameters including the period of fermentation, incubation temperature, size of inoculums and addition of prebiotic (fructooligosaccharides, FOS) were studied in the fermentation. Free cell probiotic femrmentation was carried out successfully in which the amount of probiotic was increased as much as 4.2 log cfu/mL after the juice was fermented for 2 day at 37oC. A minimum of 1% (v/v) probiotic can be inoculated into the juice to product the same amount of cell increment. The cell increment after fermentation can be further improved to 5 log cfu/mL by adding 1% (w/v) FOS into red dragon fruit juice. Viability loss of 1.2 log cfu/mL of probiotic in fermented red dragon fruit juice was observed after 4 week storage at 4oC. The viability loss can be reduced by microencapsulated the probiotic bacteria in alginate. In terms of microencapsulation,parameters such as period of fermentation, addition of second coating in microencapsulation, amount of cell load in alginate beads and concentration of calcium alginate beads were studied. The results of probiotic microencapsulation was promising in which lesser viability loss of probiotic (0.5 log cfu/g) was observed in red pitaya juice fermented with encapsulated L. casei after 4 week storage at 4oC when comparing to free cell L. casei fermented juice. The viability loss of encapsulated probiotic in red dragon fruit juice can be further improved with 1% (w/v) calcium alginate beads with 107 to 109 cfu/g of probiotic in the beads. Viability loss was reduced to as low as 0.07 log cfu/g in fermented red dragon fruit juice with microencapsulated probiotic and the results were much better than free cell probiotic which reduced 2.2 log cfu/g after stored at 4oC for 4 week. Fermentation of red dragon fruit juice with free cell and microencapsulated probiotic showed no adverse effect on the physico-chemical characteristics especially the antioxidant properties of,red dragon fruit juice. The development of probiotic beverage in red dragon fruit juice prolonged the shelf-life of the fruit as well as transforming the fruit juice into a healthy beverage that contains high antioxidant properties (total phenolic content: 29.6 to 31.42 mg/L gallic acid equivalent, ABTS+• inhibition: 12% to 13.1%) and probiotic. In addition, the red dragon fruit juice based probiotic drink is suitable for individuals that are milk allergic and lactose intolerant.